Factors Affecting Cellulose Dissolution of Oil Palm Empty Fruit Bunch and Kenaf Pulp in NaOH/Urea Solvent - Khairunnisa Waznah Baharin; Sarani Zakaria; Ellis, Amanda V.; Noraini Talip; Hatika Kaco; Sinyee Gan; Farrah Diyana Zailan; Sharifah Nurul Ain Syed Hashim (Penerbit UKM, 2024)
Volume :47 Number: 2